Road vehicle accident reconstruction - Dukkipati, Rao V. (Anshan, 2014)
This book is a comprehensive guide to the reconstruction of road vehicle accidents. Its objective is to provide the guidance to solving complex road accident problems using mathematical modeling and to evaluate methods for computing numerical results from given data. Each chapter in this book consists of a concise but thorough fundamental statement of the problems, methods and solutions, and the author keeps the balance between theory and practical application. The book will be of value to a very wide number of professional fields, as well as to academics and students: in mathematics, science, engineering, law, vehicle manufacturers and suppliers, police departments and academies, and insurance companies, and of course professionals involved in accident reconstruction.